2012
DOI: 10.1097/spv.0b013e3182673772
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Sacral Hysteropexy

Abstract: The ASH offers advantages and disadvantages that warrant further investigation with a prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…There was no evidence of publication bias with the Egger test for reoperation for POP recurrence (P5.521) (Appendix 5, http://links.lww.com/ AOG/C307). A meta-analysis found an increased risk of mesh exposure with hysterectomy and sacrocolpopexy compared with sacrohysteropexy (open 66,70 or laparoscopic 74 ) at 1.6-4.25 years (7.5% vs 0%; RR 9.74, 95% CI 1.26-75.21; I 2 0%; three studies, one excluded from meta-analysis; n5197) (low). 66,70,74 Other comparisons and results for hysterectomy and suspensions compared with hysteropexy are in Appendix 6 (http://links.…”
Section: Resultsmentioning
confidence: 99%
“…There was no evidence of publication bias with the Egger test for reoperation for POP recurrence (P5.521) (Appendix 5, http://links.lww.com/ AOG/C307). A meta-analysis found an increased risk of mesh exposure with hysterectomy and sacrocolpopexy compared with sacrohysteropexy (open 66,70 or laparoscopic 74 ) at 1.6-4.25 years (7.5% vs 0%; RR 9.74, 95% CI 1.26-75.21; I 2 0%; three studies, one excluded from meta-analysis; n5197) (low). 66,70,74 Other comparisons and results for hysterectomy and suspensions compared with hysteropexy are in Appendix 6 (http://links.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 Ridgeway 18 concluded that the advantages of the uterine-sparing POP procedure include shorter operative time, reduced blood loss, quicker recovery, fertility preservation, avoidance of unnecessary hysterectomy and minimization of surgical risks, maintenance of pelvic stability and sexual satisfaction, and diminished risk of mesh exposure. 15,20,[27][28][29][30] Other disadvantages include subsequent hysterectomy might be difficult, the ongoing risk for cervical or endometrial neoplasm, and the need of longterm surveillance for gynecological cancers. 18 Additionally, a recent meta-analysis 15 analyzed nine non-RCT studies comparing mesh sacrohysteropexy with hysterectomy plus mesh sacrocolpopexy via either an open abdominal or laparoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, minimally invasive sacrocolpopexy had a significant outcome in overall objective recurrence (pooled risk ratio [RR], 0.59; 95% CI, 0.47-0.75) and objective posterior recurrence (pooled RR, 0.59; 95% CI, 0.44-0.80) than open abdominal sacrocolpopexy. 4 Furthermore, among the minimally invasive sacrocolpopexy procedures, Chang et al 20 and Yang et al 38 also conducted systematic reviews and meta-analyses to study the effectiveness and outcomes of sacrocolpopexy using a laparoscopic or robotic approach. They found that robotic sacrocolpopexy was associated with significantly less blood loss, lower conversion rate, similar perioperative complications, and postoperative symptoms, as well as comparable anatomical outcomes and objective recurrence at a median of 6 to 12 months postoperative follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations